2015
DOI: 10.1021/ja511389q
|View full text |Cite
|
Sign up to set email alerts
|

High Anhydrous Proton Conductivity of Imidazole-Loaded Mesoporous Polyimides over a Wide Range from Subzero to Moderate Temperature

Abstract: On-board fuel cell technology requires proton conducting materials with high conductivity not only at intermediate temperatures for work but also at room temperature and even at subzero temperature for startup when exposed to the colder climate. To develop such materials is still challenging because many promising candidates for the proton transport on the basis of extended microstructures of water molecules suffer from significant damage by heat at temperatures above 80 °C or by freeze below -5 °C. Here we sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
133
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 235 publications
(135 citation statements)
references
References 78 publications
2
133
0
Order By: Relevance
“…Surprisingly, [1⊃pz⋅6 HCl] exhibits considerably high conductivity both under anhydrous and humid conditions at ambient temperature ( σ =9.7×10 −6 S cm −1 at 0 °C and 0 %RH; σ =2.48×10 −3 S cm −1 at 25 °C and 40 %RH; Figure S14 and Table S3 in the Supporting Information), which is a less‐common but potential characteristic of MOF‐based materials . Furthermore, its conductivity steeply increases upon increment of temperature up to the measured maximum temperature, 80 °C (Figure d and Figure S13 in the Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Surprisingly, [1⊃pz⋅6 HCl] exhibits considerably high conductivity both under anhydrous and humid conditions at ambient temperature ( σ =9.7×10 −6 S cm −1 at 0 °C and 0 %RH; σ =2.48×10 −3 S cm −1 at 25 °C and 40 %RH; Figure S14 and Table S3 in the Supporting Information), which is a less‐common but potential characteristic of MOF‐based materials . Furthermore, its conductivity steeply increases upon increment of temperature up to the measured maximum temperature, 80 °C (Figure d and Figure S13 in the Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Owing to the crucial role of the proton responsive azo group in facilitating proton conduction pathways, Tp‐Azo COF with H 3 PO 4 shows decent proton conductivity values under both hydrous (9.9 × 10 −4 S cm −1 ) and anhydrous (6.7 × 10 −5 S cm −1 ) conditions. Xiang and co‐workers found that imidazole loaded tetrahedral polyimides with mesopores and good stability could demonstrate a high anhydrous proton conductivity over a wide temperature range from −40 to 90 °C . Zang and co‐workers introduced polyoxometalates PW 12 O 40 3− into a cationic COF with high thermal and chemical stability .…”
Section: Other Applicationsmentioning
confidence: 99%
“…[15][16][17][18][19][20][21][22][23][24] Unlike semicrystalline or amorphousp olymers, the high crystallinity of MOFs is very suitable for studying protont ransport pathway and the conductionm echanism, demonstrating that protonc an transit through modified groups on the surfaceo ft he cavity (e.g., H 2 O, -SO 3 Ha nd -PO 3 H 2 )a nd guests in the cavity (e.g.,i midazole, histamine and ionic liquids). [5,16,[25][26][27][28] On the other hand, based on the outstanding advantagesofMOFs, the exploration of the practical application of electrically conductive MOFs has received extensive attention, especially in the field of chemoresistive sensors. [29][30][31][32][33][34] Representatively,D incǎ et al demonstrated an array of cross-reactive sensor for the identification of different typeso fv olatile organic compounds (VOCs).…”
Section: Introductionmentioning
confidence: 99%